The Ebbinghaus Illusion: New Contextual Effects and Theoretical Considerations. Issue 1 (February 2015) - Jaeger, Ted; Klahs, Kyle
Current accounts of the Ebbinghaus illusion emphasize either size contrast or contour interaction processes. To assess these alternatives, four variants of the Ebbinghaus figure were constructed using 1, 5, 9, or 13 small circles dispersed along the perimeter of larger contextual circles. 30 observers ranked the perceived size of the central circles and a single control circle. The rankings indicated that increasing the number of small circles reduced the perceived size of the central circle. The results parallel the effects of contextual arcs on the Ebbinghaus illusion and suggest that the mis-estimations of central circle size in Ebbinghaus figures result primarily from contour interactions.